Manajemen Dakwah dalam Organisasi Masyarakat : Studi Implementatif di Kecamatan Kresek, Kabupaten Tangerang - Destiyan Elviyana Nugraheni; Indah Prastika; Pangestu Nurul Alfdjiain; Aisyah Nurhakim (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This research aims to analyze the implementation of da'wah management in community organizations in Kresek District, Tangerang Regency. The research focuses on the application of da'wah management functions including planning, organizing, actuating, and controlling in da'wah activities. The research method used is descriptive qualitative with data collection techniques through observation, in-depth interviews, and documentation. The research subjects were administrators of Islamic community organizations in Kresek District. The results showed that the implementation of da'wah management in community organizations in Kresek District still requires optimization, especially in the aspects of organizing and controlling. Da'wah planning has been carried out well through the preparation of short-term and long-term work programs, but there are still obstacles in organizing human resources and coordination between organizational elements. The implementation of da'wah programs runs smoothly despite challenges in adapting to technological developments. The supervision and evaluation system needs to be improved to ensure the effectiveness of da'wah programs. This research provides recommendations for strengthening organizational management capacity through da'wah management training and developing collaboration between community organizations.